Yamuna Kachru's contributions to South Asian discourse and convergence studies. Issue 1 (March 2015) - Henrich Hock, Hans; SMITH, LARRY E.; SRIDHAR, S.N.
ABSTRACT The range of Yamuna Kachru's publications is tremendously broad, ranging from language pedagogy, to South Asian – especially Hindi – syntax and syntactic typology, to discourse in South Asian and other languages, to the broader issue of South Asia and world Englishes. This paper focuses on a number of those aspects of her work that have stimulated my own work on several facets of South Asian linguistics, and presents a personal perspective on Professor Kachru's work in this arena.